Hospice utilization among Medicare beneficiaries dying from pancreatic cancer. Issue 4 (9th July 2019) - Paredes, Anghela Z.; Hyer, J. Madison; Tsilimigras, Diamantis I.; Mehta, Rittal; Sahara, Kota; White, Susan; Dillhoff, Mary E.; Ejaz, Aslam; Cloyd, Jordan M.; Pawlik, Timothy M.
Abstract: Background: Use of hospice services among patients with pancreatic cancer following pancreatic resection remains unknown. Methods: Patients with pancreatic cancer who underwent resection were identified in the Medicare Standard Analytic Files. Outcomes included overall hospice use, early hospice enrollment (≥4 weeks before death), late hospice enrollment (initiation within 3 days of death), and Medicare expenditures. Results: Among the 4369 deceased individuals, three‐fourths of patients (n = 3252, 74.4%) used hospice at the time of death. Patients who did not use hospice were more likely to be male, have a complication on index admission and receive life sustaining treatments on subsequent admissions ( P < .05). Only one‐third (32.2%) of patients initiated hospice services early. Medicare expenditure during the last month of life was 10 000 lower among patients who initialized hospice services at least 1 month before death versus within 3 days of death (late: 10 581 [5454‐17 200], early: 221 [46‐733]; P < .001) Conclusion: While three‐fourths of patients utilized hospice services after pancreatic resection, only one‐third of patients initiated hospice services at least one‐month before death. Late hospice use was associated with higher Medicare expenditures during the last month of life. Further research is needed to understand barriers to early hospice utilization.